2020
DOI: 10.1101/2020.06.01.128306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physiological noise modeling in fMRI based on the pulsatile component of photoplethysmograph

Abstract: The blood oxygenation level-dependent (BOLD) contrast mechanism allows someone to non-invasively probe changes in deoxyhemoglobin content. As such, it is commonly used in fMRI to study brain activity since levels of 10 deoxyhemoglobin are indirectly related to local neuronal activity through neurovascular coupling. However, the BOLD signal is severely affected by physiological processes as well as motion. Due to this, several noise correction techniques have been developed through the years to correct for the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 107 publications
0
7
0
Order By: Relevance
“…The neural correlates of heart rate found in our work and in Valenza et al ( 29 ) were not entirely consistent, which may result from the more aggressive physiological correction applied in our work. Artifacts due to cardiac pulsatility were removed using the newly proposed cardiac pulsatility model ( 55 ) and systemic low-frequency oscillations were removed through gray matter signal regression ( 47 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…The neural correlates of heart rate found in our work and in Valenza et al ( 29 ) were not entirely consistent, which may result from the more aggressive physiological correction applied in our work. Artifacts due to cardiac pulsatility were removed using the newly proposed cardiac pulsatility model ( 55 ) and systemic low-frequency oscillations were removed through gray matter signal regression ( 47 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that head and breathing motion affect areas at the edges of the brain (Jo et al, 2010; Patriat et al, 2015; Satterthwaite et al, 2013), whereas cardiac pulsatility affects areas near the large cerebral arteries just above the neck (Glover et al, 2000; Kassinopoulos and Mitsis, 2020). These observations are based on studies that typically examine the brain regions affected by the aforementioned sources of noise on a voxel-wise basis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the GS derived either by the whole brain or GM are very similar to each other and also that the GS is highly correlated with the mean time series across voxels in WM and CSF (Kassinopoulos & Mitsis, 2019; Power et al, 2017), which further lends support to the idea that WM regressors share common variance with the GS. Furthermore, we observed that the SLFOs that reflect BOLD fluctuations due to changes in heart rate and breathing patterns, and account for a significant fraction of GS fluctuations (Falahpour et al, 2013; Kassinopoulos & Mitsis, 2019, 2020), were well explained using the first 20-30 WM and CSF regressors (Fig. 1).…”
Section: Discussionmentioning
confidence: 80%
“…Despite the simplicity of GSR, there has been much debate about its use (Liu et al, 2017; Murphy & Fox, 2017). Even though several studies have shown that a large fraction of the GS is associated to physiological processes such as heart rate and breathing activity (Birn et al, 2006; Chang et al, 2009; Falahpour et al, 2013; Kassinopoulos & Mitsis, 2019, 2020; Shmueli et al, 2007; Wise et al, 2004) as well as head motion (Power et al, 2014; Satterthwaite et al, 2013), there is accumulating evidence that GS is also driven by neuronal activity as assessed by intracranial recordings (Schölvinck et al, 2010) and vigilance-related measures (Chang et al, 2016; Falahpour et al, 2018; Liu & Falahpour, 2020; Wong et al, 2013, 2016). Therefore, while our results are in support of GSR for both WM and FIX denoising, we cannot exclude the possibility of removing some neuronal-related fluctuations from the data when the GS is removed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation